STRATEGI PEMASARAN JASA PENDIDIKAN DALAM MENINGKATKAN CITRA SEKOLAH DI SDN 2 ARGOMULYO DESA ARGOMULYO KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Mamlukhah Mamlukhah; Weni Wahidatun Nufusiah (Institut Agama Islam Darussalam Blokagung, 2021)
This study aims to determine the marketing strategy of educational services at SDN 2 Argomulyo Village, Sumberejo District, Tanggamus Regency, Lampung Province. The research method used is descriptive qualitative, with a case study approach. Regarding the data collection procedure, by means of observation, interviews and documentation, then the validity of the data is tested, through credibility, transferability, dependability, and confirmability tests. The data analysis tool used is IFAS, EFAS and SWOT analysis. The results show that the marketing strategy of educational services used by SDN 2 Argomulyo in exploiting the strengths of the opportunities that have been identified: the school optimizes teacher performance, maintains the good name of the school, strengthens the good name of the school in the community. In minimizing weaknesses to take marketing model and create a more attractive extracurricular style. In minimizing weaknesses in order to avoid threats: conducting teacher training programs, disseminating the name of the school when entering the field and optimizing marketing in all media. The conclusion of the study shows that the marketing strategy carried out by the school is not optimal, causing many obstacles. The main factor of the constraints on the marketing of educational services is due to the zoning system and parents prefer to send their children to schools that are closer to home.